The rise of common state ownership and corporate environmental performance - Liu X; Boubaker S; Liao J; Yao S (Elsevier Ltd, 2024)
This study assesses the effect of common state ownership on corporate environmental performance. Using a large sample of Chinese listed firms, we find that state-owned common ownership leads to significantly enhanced corporate environmental performance. Our mechanism analysis indicates that state-owned common owners promote environmental-friendly practices through resource allocation mechanisms that alleviate corporate financial constraints. In addition, these owners play a leadership role in fostering corporate green innovation and enhancing the overall performance of the industry. Specifically, common state ownership leads to higher industry's green total factor productivity and profitability. Moreover, we observe that the positive relationship between common state ownership and corporate environmental performance is more pronounced in firms without politically connected CEOs/chairpersons and in privately owned firms.
Keywords: Common state ownership; Government social objective; Leadership role; Corporate environmental performance; China